The use of Learning Management System (LMS) in distance learning program for in-service teachers: exploring teacher-learner interaction - Abdul Talib, Mohd. Fairuz (2014)
Interaction procedures have been touted as an important element in the utilization of Learning Management Systems (LMS’s) to support distance learning, in reducing physical distance between students and instructors. Four types of interaction have been suggested to take place in the LMS’s, and previous studies have identified that teacher-learner interaction is usually missing, the lack of which has been reported as the source of frustration among learners. This study explored teacher-learner interaction in the use of LMS in an in-service teacher distance learning program. Two Malaysian university lecturers of the said program were interviewed, and the interviews were transcribed and thematic analysis technique was used to highlight key themes to answer the research questions. The findings revealed that lecturers perceived teacher-learner interaction as very important. Usages of LMS which promote interaction were identified, as well as the challenges, and the factors contributing to successful promotion of interaction.